Development of Interactive Infographic Media Assisted by Google Sites with Cooperative Learning Model for Elementary School Students - Rosyada, Dini Alya; Raharjo, Makmum; Suratmi, Suratmi (Universitas Pendidikan Mandalika, 2025)
This study aims to develop interactive infographic learning media based on Google Sites that integrates cooperative learning models on food chain material for fifth grade elementary school students. The type of research used is development research with the ADDIE model consisting of the stages of Analysis, design, development, implementation, and evaluation. Data collection techniques used are observation, interviews, documentation, needs analysis, validation sheets, response questionnaires, and tests. The results of this study indicate that interactive infographic learning media based on Google Sites is effective and practical to use, with an N-gain score reaching 0.838452, which is included in the high category. This study shows that interactive infographic media can improve students' understanding of concepts and mastery of material, so it is suitable for use in the learning process.